The gesture–language association over time in toddlers with and without language delays. (May 2019) - Manwaring, Stacy S; Swineford, Lauren; Mead, Danielle L; Yeh, Chih-Ching; Zhang, Yue; Thurm, Audrey
Background and aims: Young children with language delays or other factors that heighten risk for autism spectrum disorder often show reduced gesture use. In particular, deictic gestures such as pointing and showing are reported to be deficient in young children with autism spectrum disorder, and their use has been found to predict expressive vocabulary development. The first aim of this study was to examine the production of two types of gestures (deictic and conventional) for two communicative functions (behavior regulation and joint attention) across two observational contexts in a sample of 18-month-old toddlers with significant language delays compared to typical controls. The second aim was to examine if and how gesture use (type and communicative function) at 18 months is associated with later receptive and expressive language. Methods: Toddlers with significant language delays ( n = 30) or typical development ( n = 62) were drawn from longitudinal studies of early language delay as a risk factor for autism spectrum disorder. Toddlers identified with early language delay were classified based on a diagnosis of autism spectrum disorder ( n = 12) or non-autism spectrum disorder ( n = 18) after an evaluation at 36 months. Gestures were coded from video recordings of the Communication and Symbolic Behavior Scales Developmental Profile–Behavior Sample and a naturalistic parent–child interaction obtained at 18 months. Language outcomes included receptive and expressive age equivalents from the Mullen Scales of Early Learning and the number of words produced on the MacArthur–Bates Communicative Development Inventories. Results: At 18 months, toddlers with language delay showed reduced deictic and conventional gesture use in both the Communication and Symbolic Behavior Scales Developmental Profile–Behavior Sample and parent–child interaction compared to toddlers with typical development. Within the language delay group, toddlers with an autism spectrum disorder diagnosis at outcome also produced significantly fewer deictic gestures than those without an autism spectrum disorder diagnosis across both communicative functions and observational contexts. While all groups of toddlers gestured more in the Communication and Symbolic Behavior Scales Developmental Profile–Behavior Sample, the mean difference in gesture use between the Communication and Symbolic Behavior Scales Developmental Profile–Behavior Sample and parent–child interaction was significantly larger in toddlers with typical development than language delay for deictic gestures, as compared to the difference between the two contexts for conventional gestures. In the combined sample, a significant association was found between deictic gestures used in the Communication and Symbolic Behavior Scales Developmental Profile–Behavior Sample and change in the number of words produced from 18 to 36 months, accounting for significant demographic and developmental confounders. Conclusions: Findings show that early language delay is associated with reduced deictic and conventional gestures across observational contexts. Importantly, deictic gesture use, but not conventional, was associated with the development of expressive language in toddlers with and without language delays. Implications: Deictic gestures play an important role in the development of expressive language in toddlers, including those with language delays. Assessment of young children with language delays should include evaluation of types of gestures used and communicative function of gestures, with assessments utilizing communicative temptations yielding higher rates of gesture production. Directly targeting both gesture type and function in early intervention may be important in facilitating the development of language.